1983
DOI: 10.1038/icb.1983.24
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Antibiotic Resistance in a General Hospital: A Two Year Survey

Abstract: Summary. For two years transferable antibiotic resistance (TAR) was studied by replicator methods in strains of Enterohacteriaceae isolated in a 900-becI hospital. Transfer to an Escherichia coli recipient was demonstrated in 21% of 7,800 Enterobacteriaaae. Il was most common in Klebsiella (37% of isolates) and least in Acinetobacter (G%). The mean number of phenotypic resistance markers (RMs) transferred was higher from Klebsiella pneumoniae or Enterobacter cloacae than from E. coli or P. mirabilis. K. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Earlier studies on a collection of gentamicin-resistant enterobacteria from this hospital and other hospitals in Australia have been limited to descriptions of the patterns of different resistance genes that are transferred by conjugation and have not differentiated between genes that confer resistance to the same antibiotic (1). These studies could not include resistance genes found on nonconjugative plasmids or on the chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on a collection of gentamicin-resistant enterobacteria from this hospital and other hospitals in Australia have been limited to descriptions of the patterns of different resistance genes that are transferred by conjugation and have not differentiated between genes that confer resistance to the same antibiotic (1). These studies could not include resistance genes found on nonconjugative plasmids or on the chromosome.…”
Section: Discussionmentioning
confidence: 99%